Sistem E-Customer Relationship Management Berbasis Web untuk Pengelolaan Pelanggan - Nur Sabrina; Dewi Anggraeni; Akmal Nasution (Institut Teknologi Garut, 2026)
Advances in information technology are driving businesses to utilize digital systems to improve the quality of customer service. Cafe Kekynian, as a culinary business, still faces challenges in managing customer data and transactions, which were previously handled manually, making it difficult to record transaction histories and monitor customer activity. This study aims to design and implement a web-based Customer Relationship Management (CRM) system to support more effective customer relationship management. The research method employed is software engineering using the Software Development Life Cycle (SDLC) approach, which includes the stages of requirements analysis, system design, implementation, and system testing. Research data was obtained through observation, interviews, and documentation conducted at Cafe Kekynian. System testing was performed using the Black Box Testing method to ensure that every system function operates in accordance with user needs. The results of the study indicate that the developed CRM system is capable of integrating customer data management, transaction recording, and purchase history storage into a single centralized database. The implementation of this system facilitates managers in monitoring customer activities, improves the efficiency of transaction data management, and supports the formulation of more effective customer service strategies.